2021
DOI: 10.3329/bjms.v20i5.55559
|View full text |Cite
|
Sign up to set email alerts
|

Is SARS CoV-2 viral mutation leading us to a virtual world?

Abstract: not available Bangladesh Journal of Medical Science Vol.20(5) 2021 p.185-187

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The conditions established by us under which the epidemic situation with COVID-19 in the Northern part of Ukraine can be complicated confirm the conducted researches in other territories. Thus, more often the infection occurs in close communication with the patient, in families [7][8][9] . The most vulnerable risk group was the elderly 22,23 , which was confirmed by us.…”
Section: Ethical Clearence: Not Requiredmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions established by us under which the epidemic situation with COVID-19 in the Northern part of Ukraine can be complicated confirm the conducted researches in other territories. Thus, more often the infection occurs in close communication with the patient, in families [7][8][9] . The most vulnerable risk group was the elderly 22,23 , which was confirmed by us.…”
Section: Ethical Clearence: Not Requiredmentioning
confidence: 99%
“…The spread of COVID-19 both within and outside the country is associated with migration, tourism, religious rites, etc. [4][5][6][7] It is reported that one patient with COVID-19 can infect 3-4 people in the cell 8 , and human-to-human transmission of the virus occurs mainly among family members, including relatives and friends who are in close contact with the patient 9,10 . At the same time, the spread of SARS-CoV-2 virus depends on the nature and speed of radical restrictive measures (observation, isolation, quarantine) at the national, regional and local levels, the use of personal protective equipment and social responsibility [11][12][13][14] .…”
Section: Introduction: Coronary Heart Disease In 2019mentioning
confidence: 99%
“…Improved planning as well as the continued development and launch of effective vaccines and treatments are essential to prevent successive waves of COVID-19, with for instance the second wave seen to have a devastating effect among different states in India 75 . Improved surveillance of emerging strains can also enhance future preventative measures including the development of new vaccines where pertinent 76 .…”
Section: The Instigation Of Large Multi-arm Studies Including the World Health Organisation (Who) Solidaritymentioning
confidence: 99%
“…For individuals inexperienced with the complexities of virtual learning, this endeavour has proved difficult, adding both workload and stress at an already stressful time. 2 Burnout has been widely studied in clinical nursing practice but has received little attention in nursing faculty (Thomas et al, 2019;Yedidia et al, 2014). 3,4 Regardless of setting, burnout is characterized by feelings of emotional exhaustion, depersonalization, and a low sense of personal accomplishment resulting from conditions in the workplace (Dolan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%